2014
DOI: 10.5007/1984-6924.2014v11n1p89
|View full text |Cite
|
Sign up to set email alerts
|

Atentados à liberdade de expressão? Uma análise dos casos de violência contra jornalistas no Brasil

Abstract: Federal do Maranhão. Pesquisa elites culturais e políticas; jornalismo investigativo; intersecção entre jornalismo, literatura e política.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0
1

Year Published

2021
2021
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 0 publications
0
3
0
1
Order By: Relevance
“…The study is located in Mexico and Brazil, countries where severe risks to journalists and the ability of some to continue their work are well documented (National Federation of Journalists 2018; del Palacio Montiel, Gómez Rodríguez, and Salazar Rebolledo 2020; . Though on this note, the risks that journalists experience vary significantly across both Mexico and Brazilian states (Brambila and Hughes 2019; González de Bustamante and Relly 2021;Melo and Gomes 2014). Our comparative design takes advantage of the territorial variation in risk within national media systems that have broad similarities in political regime, territorially uneven presence of organized crime, and longer-term politicaleconomic pressures by leveraging comparison on key contextual threats for journalist safety, occupational autonomy, and public-interest professionalism.…”
Section: Study Design and Recruitmentmentioning
confidence: 99%
“…The study is located in Mexico and Brazil, countries where severe risks to journalists and the ability of some to continue their work are well documented (National Federation of Journalists 2018; del Palacio Montiel, Gómez Rodríguez, and Salazar Rebolledo 2020; . Though on this note, the risks that journalists experience vary significantly across both Mexico and Brazilian states (Brambila and Hughes 2019; González de Bustamante and Relly 2021;Melo and Gomes 2014). Our comparative design takes advantage of the territorial variation in risk within national media systems that have broad similarities in political regime, territorially uneven presence of organized crime, and longer-term politicaleconomic pressures by leveraging comparison on key contextual threats for journalist safety, occupational autonomy, and public-interest professionalism.…”
Section: Study Design and Recruitmentmentioning
confidence: 99%
“…A segunda parte do que se compreende como estrutura da linguagem está baseada num conjunto de autores que mostram formas de construção das postagens que deixam de lado a qualidade do conteúdo, mas que atiçam o leitor a clicar no conteúdo, especialmente motivados pela curiosidade, pelo direcionamento ou pela ausência de informação (Nguyen, 2016;Orosa et al, 2017;Gomes;Costa, 2016;Bazaco et al, 2019). Aqui são 10 categorias que podem aparecer de forma concomitante: uso de pronomes catafóricos ou de referência antecipada; utilização de verbos no modo imperativo; modo verbal interrogativo que leva à interação; construções textuais com sentido incompleto/ocultação informação e gerando curiosidade e mistério; reportagens em formato de lista numerada; frases nominais ou de estrutura simples; coloquialismos e gírias e, por fim, uso de pontuação e exclamações, hashtag e palavras-chave.…”
Section: Abordagem Metodológicaunclassified
“…3 A general study on freedom of expression conducted by Melo and Gomes (2014) found that murders, threats, and assaults are often aimed at journalists that work in local media outlets, particularly media outlets in smaller cities. Among the statistics of murdered journalists, they also found that victims maintained very close or conflicting relations with politicians and businessmen.…”
Section: Victimization In Brazilmentioning
confidence: 99%
“…The study is located in Mexico and Brazil, countries where severe risks to journalists and the ability of some to continue their work are well documented (National Federation of Journalists 2018; del Palacio Montiel, Gómez Rodríguez, and Salazar Rebolledo 2020; Hughes and Márquez-Ramírez 2017). Though on this note, the risks that journalists experience vary significantly across both Mexico and Brazilian states (Brambila and Hughes 2019; González de Bustamante and Relly 2021;Melo and Gomes 2014). Our comparative design takes advantage of the territorial variation in risk within national media systems that have broad similarities in political regime, territorially uneven presence of organized crime, and longer-term politicaleconomic pressures by leveraging comparison on key contextual threats for journalist safety, occupational autonomy, and public-interest professionalism.…”
Section: Study Design and Recruitmentmentioning
confidence: 99%